Studi Penambatan Molekuler dan Prediksi ADMET Senyawa Bioaktif Beberapa Jamu Indonesia terhadap SARS-CoV-2 Main Protease (Mpro) - Sheniez Adhitya Yasin; Alya Azzahra; Norman Emil Ramadhan; Vega Mylanda (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2020)
The novel coronavirus SARS-CoV-2 continues causing viral respiratory illness, known as Coronavirus Disease-2019 (COVID-19). COVID-19 is considered as the biggest global pandemic disease in 2020 and its antiviral therapies are still lacking worldwide. Current studies are still trying to find potential therapies of the disease, including from natural compounds. Therefore, it is important to acknowledge what the most effective herbs’ compounds can be used against the virus. Jamu is traditional medicine from herbs in Indonesia that possesses some medicinal properties. This research was done to find and explore the potential of Indonesian jamus as novel COVID-19 treatment. 283 bioactive compounds from Indonesian jamus were screened with ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) predictions and Lipinski’s Rule of Five parameters using ProTox-II and SwissADME. The 12 screened compounds then continued to be tested through molecular docking against SARS-CoV-2 Main Protease (Mpro) using AutoDock Vina. The result of our study showed that Curcuminol D has the lowest binding free energy of -6.9 kcal/mol and Ki (inhibition constant) of 2.99 µM compared to the other screened compounds. However, none of the screened compounds has lower binding free energy than the positive controls’, which valued -8.2 kcal/mol (Lopinavir) and -7.8 kcal/mol (Ritonavir). Despite their unfulfilled parameters, the other 271 compounds might have higher potential than the standard drugs. Therefore, the finding in the present study can be used as a starting point in the drug discovery process from natural compounds for treating COVID-19.